مدى تطبيق الحوكمة في أداء المؤسسة الإقتصادية دراسة حالة إتصالات الجزائر - بن عمر خديجة; هباطي سارة; عبد العالي بشير (جامعة عمار ثليجي الاغواط, 2022)
Corporate governance is of great interest to institutions and regional and international organizations, especially after the financial crisis and after administrative problems such as corruption, favoritism, and lack of accountability. Hence, governance has become a fertile field for research and study. For this, the need to do research linking the relationship between corporate governance and the performance of the institution was urgent. To take advantage of its multiple advantages, as it helps to eliminate conflict and achieve harmony and balance between the interests of all parties related to the institution, in addition to tightening control over the management of companies to prevent them from abusing their authority and providing transparency. The study concluded that there is a close and positive correlation between the mechanisms of corporate governance applied in the company and the performance of the economic institution.